A case study of adapting a health insurance decision intervention from trial into routine cancer care - Miles E. Charles; Lindsay M. Kuroki; Ana A. Baumann; Rachel G. Tabak; Aimee James; Krista Cooksey; Mary C. Politi (BMC Research Notes, 2022)
Abstract Objective This study adapted Improving Cancer Patients’ Insurance Choices (I Can PIC), an intervention to help cancer patients navigate health insurance decisions and care costs. The original intervention improved knowledge and confidence making insurance decisions, however, users felt limited by choices provided in insurance markets. Using decision trees and frameworks to guide adaptations, we modified I Can PIC to focus on using rather than choosing health insurance. The COVID-19 pandemic introduced unforeseen obstacles, prompting changes to study protocols. As a result, we allowed users outside of the study to use I Can PIC (> 1050 guest users) to optimize public benefit. This paper describes the steps took to conduct the study, evaluating both the effectiveness of I Can PIC and the implementation process to improve its impact. Results Although I Can PIC users had higher knowledge and health insurance literacy compared to the control group, results were not statistically significant. This outcome may be associated with systems-level challenges as well as the number and demographic characteristics of participants. The publicly available tool can be a resource for those navigating insurance and care costs, and researchers can use this flexible approach to intervention delivery and testing as future health emergencies arise.